BIRTHING A CONTRACT: a critical evaluation of commercial surrogacy in India through a contractual framework. Issue 3 (2nd September 2017) - Kumar, Manasi
ABSTRACT: The future of commercial surrogacy is uncertain in India. While the Indian Parliament is currently considering a proposed ban on commercial surrogacy, there is strong opposition to a complete ban. Instead, it seems likely that a regulatory framework is going to be the way forward for commercial surrogacy. This paper maps the development of various proposed regulatory frameworks over the past decade, paying close attention to the form contracts drafted by the Ministry of Health and Family Welfare. In the process, suggestions are made to restructure the surrogate's compensation, the manner of payment, the termination and remedies provisions, and the disclosures contained in the form contract, in a manner which can adequately address concerns regarding the potential of exploitation of the surrogate.